A framing analysis of Canadian household food insecurity policy illustrates co-construction of an intractable problem. Issue 2 (3rd April 2018) - McIntyre, Lynn; Patterson, Patrick B.; Mah, Catherine L.
ABSTRACT: Household food insecurity (HFI), lack of access to food because of financial constraint, is a persistent and growing problem in Canada. Framing theorists Donald Schön and Martin Rein explain that in 'intractable policy controversies', policy issues that are particularly stubborn or resistant to change, the frames policy actors apply permit them to talk past each other without resolution. This paper examines how HFI is framed in Canadian legislative sessions and how the framing process renders the problem 'intractable'. We assembled verbatim extracts from the legislative session records of the Canadian federal government and the provinces of British Columbia, Nova Scotia, and Ontario from 1995 to 2012. Our framing analysis found that legislators' use of symbolic devices illuminated a foundational dispute around partisan claims of moral authority. HFI has thus become so imbued with irreconcilable conflict that rival parties have co-constructed it as an intractable policy problem resulting in scant policy solutions.